Study the Effect of Oxides Emitted from the Smoke of Bakeries on the Density of Bone - Reham K.H. Ibrahim (Journal of Global Pharma Technology, 2019)
Objectives: Osteoporosis is bone disorders that excess a person’s dangers of fracture due to low bone mineral density, impaired bone microarchitecture/mineralization, & diminution bone strength. This asymptomatic condition often remains undiagnosed until it manifests as a low-trauma fracture of the hip, spine, proximal humerus, pelvis, & wrist, which frequently leads to hospitalization. Methods: The present study of 41 bakeries worker’s various places in Baghdad. Serum levels of vitamin D3, PTH hormone, Calcium, magnesium and phosphorus were measured and analyzed of the bakeries smoke resulting from the combustion of kerosene substance by a device (aeroqual).Results: a significant increase in serum level of parathyroid hormone in bakery workers' group when the compared to a healthy control group (P=0.003). a slightly decrease of vitamin D3 in bakery worker groups as compared with a healthy control group, but it was not significant differences (p=0.068). Calcium, magnesium & phosphorus were determined in sera of healthy control group & bakery workers' group as It is clear that, there is no significant variation in the calcium & magnesium concentrations between control group and bakery workers' group (p=0.612), (p=0.748), respectively, while a significant decrease in the phosphorus concentrations, in bakery workers' group as compared to a healthy control group. This result showed that there was an appositive correlation between magnesium and years of work. Conclusion: It is possible to predict the risk of osteoporosis in bakeries bone by measuring levels of vitamin D3, PTH and bone minerals (Ca, Mg, and phosphorus) in their sera, and measuring the toxic oxides concentrations (NO2 and CO) emitted from the smoke of bakeries resulting from combustion of kerosene used as fuel.Keywords: Osteoporosis; Vitamin 25 (OH) D3, PTH hormone, Magnesium.